An analysis of pedestrian preferences for wayfinding signage in urban settings: evidence from Nanning, China - Zhou, Jialu; Ujang, Norsidah (Multidisciplinary Digital Publishing Institute, 2024)
As global urbanization accelerates, the integration, readability, and connectivity of urban spaces are becoming focal points of international concern, particularly in rapidly developing regions like Asia. The inadequacies of urban wayfinding systems directly affect pedestrians’ wayfinding experiences within city spaces. Pedestrian wayfinding signage, as a critical element supporting pedestrian navigation and urban readability, is often neglected in vehicle-centric urban planning. This study explores the visual preferences of pedestrians regarding wayfinding signage and how these perceptions can be incorporated into the design process. A photo-based survey consisting of 385 pedestrians in Nanning, China, reveals that while many wayfinding signs provide cognitive information, they score lower in visual preference due to poor sensory perception and difficulty in conveying meaning. This study also highlights that the material, color, graphics, and text on signage are key physical attributes influencing the visual preferences of pedestrians. Demographic factors such as age, gender, and professional background also impact these preferences. These findings underscore a broader urban design issue: wayfinding signs must not only clearly communicate navigational information but also enhance the aesthetic and cultural expressions of urban spaces. Current signage systems often neglect these aesthetic and cultural needs, potentially leading to visual fatigue or cultural disconnection, thereby affecting navigation efficiency and urban experience. The results provide empirical foundations for optimizing wayfinding signage designs in urban areas, aiding urban planners and designers in integrating pedestrian preferences to create clearer, more attractive navigation systems, thus improving walking experiences and significantly enhancing the daily lives of city residents.